On the single-root approach within the framework of coupled-cluster theory in fock space - Horny, L; Schaefer, HF; Hubac, I; Pal, S (Chemical Physics, 2005)
A thorough formulation of Fock Space Brillouin-Wigner Coupled Cluster method is presented following previous developments [N.D.K. Petraco, L Horny, H.F. Schaefer, I. Hubac, J. Chem. Phys. 117 (2002) 9580]. The new method is designed to avoid the intruder states problem, and introduces the single-root solution feature which has not been considered yet within valence-universal methods. The explicit equations for the (0,1) sector of the Fock space are introduced. (C) 2005 Elsevier B.V. All rights reserved.